Level of Patient Satisfaction in Nursing Services in the Inpatient Room of Ende Regional Hospital - Irwan Budiana; Intan Kristina Londa (JURNAL KESEHATAN PRIMER, 2019)
Background: Nursing services are a very important part of health services in hospitals. Besides being the largest population, nursing service is a comprehensive service that includes biopsychososiocultural and spiritual aimed at individuals, families, groups and society. The most often expressed patient dissatisfaction in relation to the attitudes and behavior of the nurse profession, including delays in service, attitudes and ethics and other service quality. The purpose of this study was to determine the level of patient satisfaction with nursing services in the inpatient hospital of Ende’s Hospital. This type of research is descriptive with survey research design. The population in this study were all patients treated in the inpatient room of Ende’s Hospital totaling 249 people. The sampling technique was purposive sampling with a total sample of 75 people. The results showed 28 people (37.3%) were less satisfied with wound care and 33 people (44.0%) were quite satisfied with individual hygiene or bathing. Conclusion that the majority of patients, as many as 45 people (60.0%) were quite satisfied with nursing services in the inpatient room of Ende’s Hospital, 21 people (28.0%) were less satisfied and 9 people (12.0%) were satisfied. Nursing officers are expected to always provide opportunities for patients and families to participate in the care process and further enhance their skills and always provide services in a friendly manner and prioritize ethics in service.